How to enable ambidexterity in safety-critical software development - Turner, Neil; Baxter, David (Taylor & Francis, 2024)
In a competitive environment, continually improving new products and services requires new knowledge and novel solutions. Managing projects also requires the careful control of resources for effective delivery. Ambidexterity, the simultaneous achievement of novelty through exploration and efficiency through exploitation, is challenging to achieve in practice. The ways in which companies can achieve ambidexterity are context dependent. It is especially hard to promote new and uncertain concepts in situations where lives are at stake. This article reports on a case study of a safety-critical IT development project that successfully achieved ambidexterity. Leadership behaviors that support ambidexterity in this setting are critical. We highlight four leadership behaviors key to developing an environment where creative solutions can flourish.
Keywords: Ambidexterity; Safety critical; Project management; Agile; Software development